(untitled) (International journal of artificial intelligence, 2026)
The main purpose of this scientific work is to study the technology of developing students' critical thinking skills and analyze its importance in the educational process. Critical thinking skills are activities aimed at developing students' analytical and independent thinking skills in the process of analyzing, evaluating, comparing information, finding solutions to problems and drawing conclusions. The use of modern educational technologies is important for developing students' critical thinking skills. This work focuses on the basic principles, methods and techniques for developing critical thinking. In particular, technologies such as asking logical and critical questions, using analytical and evaluative approaches, and encouraging creative thinking to solve problems are highlighted. The role of the teacher in the formation of critical thinking in students, the effectiveness of interactive lessons and group work are also analyzed. Developing critical thinking helps students not only succeed in education, but also make independent decisions in life, effectively solve problems, and develop logical thinking. Therefore, the practical application of critical thinking development technologies in the education system will greatly contribute to improving the quality of education in the future. This article is aimed at studying the scientific and practical foundations and effective methodologies for developing students' critical thinking skills, which will serve to increase the effectiveness of the use of these technologies in educational institutions.